(untitled) (Sir Salimullah Medical College Journal, 2023)
Background: To evaluate the effectiveness of High Flow Nasal Cannula (HFNC) and standard non rebreathing mask (NRBM) as oxygen delivery device, in moderate cases of COVID-19 Pneumonia. Methods: A single-centre, prospective analysis conducted at KBFGH. Eighty enrolled patients were randomly divided into two groups according to the oxygen delivery device used. Group 1 (n = 40) received HFNC and group 2 (n = 40) received NRBM as initial oxygen delivery device, to maintain a target saturation of e” 96% in both groups. The success rate of oxygen therapy, time to progression to severe disease, PaO2, PaO2/FiO2 ratio, respiratory rate, heart rate, blood pressure, number of patients requiring NIV or endotracheal intubation, time for de-escalation of oxygen therapy to lower Fio2 device and patient satisfaction level were compared among the two groups. Results: Demographic, clinical variables and treatment given were comparable in the two groups. In the HFNC group 83.3% patients had successful outcomes with the initial oxygen therapy device used as compared to 66.6% in the NRBM group. However, the use of HFNC resulted in improved oxygenation (P < 0.001), better patient satisfaction (P < 0.001) and shorter time for de-escalation of oxygen therapy to a lower FIO2 device (3.75 ± 1.032 vs. 6.83 ± 0.928). Conclusions: HFNC is a reliable oxygen therapy modality for moderate category COVID- 19 pneumonia that results in better oxygenation and a greater patient satisfaction level as compared to a non-rebreathing mask. Sir Salimullah Med Coll J 2023; 31: 79-85